Penggunaan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Siswa Kelas 3 SD Negeri Margorejo - Sukesi Sukesi (Perkumpulan Kualitama Edukatika Indonesia, 2022)
The aim of this research is to improve the learning outcomes of 3rd grade students at Margorejo State Elementary School, Cepiring District, Kendal Regency, Mathematics Subjects, Whole Number Material, using the Problem Based Learning (PBL) Learning Model for the Odd School Year 2021/2022. This type of research is classroom action research (CAR) using cycle I and cycle II. Data collection techniques in this research were written tests, documentation and observation using cycle I and cycle II. Data analysis in this research is student learning outcomes in cycle I and cycle II by testing using statistical test learning outcomes scores. The success indicator is said to obtain maximum results if the student's test score is more than the KKM, namely 75. The success indicator used is successful if it increases by more than or equal to 85% of the total number of 3rd grade elementary school students who reach the KKM, namely 75. The results of this research occur increasing student learning outcomes from cycle I to cycle II and achieving classical learning completeness in cycle II.